Foraging Habitat and Chick Diets of Roseate Tern, Sterna dougallii, Breeding on Country Island, Nova Scotia - Jennifer C. Rock; Marty L. Leonard; Andrew W. Boyne (Avian Conservation and Ecology, 2007)
Breeding seabirds are threatened by human activities that affect nesting and foraging habitat. In Canada, one of the seabirds most at risk of extirpation is the Roseate Tern, Sterna dougallii. Although critical nesting habitat has been identified for the Roseate Tern in Canada, its foraging locations and the diet of its chicks are unknown. Therefore, our goal was to determine the foraging locations and diet of chicks of Roseate Tern breeding on Country Island, Nova Scotia, which is one of Canada's two main breeding colonies. In 2003 and 2004, we radio-tracked the Roseate Tern by plane to locate foraging areas and conducted feeding watches to determine the diet of chicks. Roseate Tern foraged approximately 7 km from the breeding colony over shallow water < 5 m deep. In both years, sand lance, Ammodytes spp., was the most common prey item delivered to chicks, followed by hake, Urophycis spp. Our results are consistent with previous work at colonies in the northeastern United States, suggesting that throughout its range, this species may be restricted in both habitat use and prey selection. The reliance on a specific habitat type and narrow range of prey species makes the Roseate Tern generally susceptible to habitat perturbations and reductions in the availability of prey.